Peningkatan pengetahuan, sikap, dan psikomotorik melalui pembekalan duta Usaha Kesehatan Sekolah (UKS) SMK Kesehatan Binatama Yogyakarta - Kristina, Santy Dwi; Suprapto, Kartina Catur Agung; Astuti, Silvia; Natapraja, Dwi; Indriani , Meyke Herlin; Mirza, Mira Maria; Wijayanto, Taufik; Rahim, Mohammad Afiff Bin; Subagja, Bayu; Santri, Ichtiarini Nurullita; Kodriati, Nurul (Universitas Mataram, 2024)
Healthy behavior must be accustomed to from an early age and become a habit. At the school age, healthy living habits can be carried out by integrating health programs with school activities through School Health Business activities commonly known as School Health Units (UKS). The purpose of this community service is to provide training for class X students of SMK Kesehatan Binatama Yogyakarta as UKS Ambassador candidates and will carry out the UKS mentoring program at the junior high school level. The debriefing is carried out through an interactive method of delivering material using counseling media/tools, discussion, and simulations/direct practice. The themes given are introduction of UKS, communication, counseling methods, Three Basic ThreatsÂ Adolescent Reproductive Health (TRIAD KRR), basic health and hand washing practices, drug management guidelines and self-medication. From the pre and post test the results are the percentage of participants' knowledge and attitudes increased by 90.5%. Participants also showed an increase in psychomotor abilities through simulations/practices that were directly observed. In order to become a sustainable program, the UKS Ambassador debriefing activities can be attended by students of class XI and XII, with a longer duration of time, and presenting the UKS Advisory Team as one of the presenters.